Deficiencias normativas que se presentan en las audiencias de incumplimiento celebradas por la Gobernación de Boyacá, durante el período comprendido entre la entrada en vigencia de la Ley 1474 de 2011 y el año 2016 (2018)
This research article exposes the nature and legal framework of non-fulfillment hearings, as well as the types of penalties derived from said hearings. Subsequently, it analyzes the non-fulfillment hearings held by the Provincial Government of Boyacá, an entity that has an integrated management system which implements and monitors the contractual administrative procedures through formats proposed by the Contracting Authority. These formats were compared with the penalty and procedural guidelines established and regulated in Law 80 of 1993 and Law 1474 of 2011, as well as in contentious-administrative jurisprudence, among others, to identify possible regulatory deficiencies in which the Provincial Government  of Boyacá may incur when initiating penalty procedures. The development of this  article intends to answer the following research problem: Normative deficiencies in the non-fulfillment hearings held by the Provincial Government of Boyacá, during the period between the entry into force of Law 1474 of 2011 and 2016. For which this article will be divided into three parts, the first in which the context and legal framework of the non-fulfillment hearings is analyzed, from its nature, its background in Colombian administrative law, and its evolution to the present day, as well as the kinds of penalties that derive from this type of procedure. In the second part, we will deal with procedural and legal deficiencies that have transpired in the non-fulfillment hearings held by the Provincial Government of Boyacá in the five-year period between 2011 and 2016, to end the third part of the article, with a series of recommendations and suggestions that, in our opinion, will make more effective the non-fulfillment hearings held by the Provincial Government without putting at risk the rights that the contractor, as a collaborator of the administration, has and allowing them to effectively materialize the purpose the legislator sought with its institutionalization.